Additions to the hydroids (Cnidaria, Hydrozoa) of the Bay of Fundy, northeastern North America, with a checklist of species reported from the region - Calder, Dale R. (Zootaxa, 2017)
Two new species of hydroids, Eudendrium bleakneyi and Halecium praeparvum, are described from the Bay of Fundy. Fourteen others, Tubularia acadiae Petersen, 1990, Coryne pusilla Gaertner, 1774, Sarsia lovenii (M. Sars, 1846), Zanclea implexa (Alder, 1856), Corydendrium dispar Kramp, 1935, Rhizogeton fusiformis L. Agassiz, 1862, Bougainvillia muscus (Allman, 1863), Rhizorhagium roseum M. Sars, in G.O. Sars, 1874, Hydractinia symbiolongicarpus Buss & Yund, 1989, Eudendrium vaginatum Allman, 1863, Tiaropsis multicirrata (M. Sars, 1835), Obelia bidentata S.F. Clark, 1875, Halecium marsupiale Bergh, 1887, and Sertularella gigantea Hincks, 1874, are reported, with collection data, for the first time from the bay. All but Coryne pusilla, Rhizorhagium roseum, Eudendrium vaginatum, and Sertularella gigantea are also new to Atlantic Canada, while Zanclea implexa, Corydendrium dispar, and Halecium marsupiale are reported for the first time in the western North Atlantic. Two of those species, Hydractinia symbiolongicarpus and Obelia bidentata, are disjunct in distribution, with core populations occurring in warmer waters to the south of Cape Cod, Massachusetts. Both were discovered in Minas Basin, a hydrographically distinct embayment where surface water temperatures are much warmer during summer than in the perpetually cold lower Bay of Fundy. Rhizorhagium roseum and the subfamily Rhizorhagiinae are transferred from family Bougainvilliidae Lütken, 1850 to Pandeidae Haeckel, 1879. An annotated checklist of hydroids from the Fundy region, based on previously published reports and on new records of species, is added as an appendix. Included in the checklist are 43 species of anthoathecates and 75 species of leptothecates, referable to 30 families and 56 genera. Families with the most species were Sertulariidae (23), Haleciidae (13), Eudendriidae (11), and Obeliidae (10). Biogeographically, the aggregate hydroid fauna of the bay conforms with that occurring in other parts of the Western Atlantic Boreal Region. Halecium permodicum is proposed as a replacement name for Halecium minor Fraser, 1935, an invalid junior homonym of H. minor Pictet, 1893.